Potensi Bakteri Dari Limbah Kotoran Ternak Dalam Mendegradasi Selulosa - Fahruddin Fahruddin; Nur Haedar Nur Haedar; Mustika Tuwo (Jurnal Ilmu Alam dan Lingkungan, 2020)
Many wastes in nature made from cellulose cause problems because it is difficult to degrade, it is needs to be treated biologically by utilizing cellulase enzymes from bacteria. Some bacteria are able to degrade a cellulose compound to be used as a source of energy, there is a lot of cattle farm. The purpose of this study was to obtain bacteria that have the potential to degrade cellulose. Isolation of cellulolytic bacteria from cattle fam waste using selective carboxymethyl cellulose media, and semi-quantitative degradation of cellulose compounds was tested. The results obtained by two cellulolytic bacteria marked the formation of inhibitory zones, in BS1 is 3.2 cm and in BS2 is 2.9 cm. From the index of inhibitory values formed, these two isolates have the ability to degrade cellulose in the average category.